A digital intervention using virtual reality helmets to reduce dental anxiety of children under local anesthesia and primary teeth extraction: A randomized clinical trial. Issue 6 (29th April 2022) - Du, Qin; Ma, Xinru; Wang, Shasha; Zhou, Shiyu; Luo, Chunmei; Tian, Kun; Fei, Wei; Liu, Xianghong
Abstract: Introduction: Behavior management of children during dental treatment is an important but challenging issue. As a new technique, VR has been applied in pediatric dental anxiety. But there is no final conclusion whether VR reduces children's dental anxiety. Methods: The aim of the study is to assess the effectiveness of a digital intervention using virtual reality (VR) helmets on dental anxiety, pain perception, and behavior triggered for children, as well as occurrence of simulator sickness in local anesthesia and primary teeth extraction. A total of 128 children, who needed primary teeth extraction under local anesthesia, were randomly allocated into two groups: use VR helmets and traditional behavior guidance procedures (control). Modified Child Fear Survey Schedule Dental Subscale (CFSS‐DS), Wong‐Baker FACES Pain Scale, Houpt Scale, and Simulator sickness questionnaire (SSQ) were used to assess children's dental anxiety, pain perception, and behavior triggered and occurrence of simulator sickness. Results: CFSS‐DS score in the VR group was significantly decreased after dental treatment (34.58±6.90 before operation and 32.32±15.58 after operation, p  = .02). The score of Wong Baker Scale in the VR group (3.47±0.76) was significantly lower than that in the control group (5.56±1.13, p  = .015). There was no significant difference in the Houpt Behavior Scale score and the SSQ score between the VR group and the control group ( p  = .35, p  = .305). Conclusion: The use of VR helmets in primary teeth extraction can significantly reduce dental anxiety and pain perception in children without occurrence of simulator sickness. Abstract :